Integration of Telkom ISP and 3 LTE Using PCC Method to Improve Internet Connection Stability - Putra, Muh. Fardika Irwan Pratama; Parenreng, Jumadi Mabe; Yahya, Muhammad (Internet of Things and Artificial Intelligence Journal, 2024)
This research focuses on improving internet connection stability at the Network Laboratory of JTIK, Faculty of Engineering, Universitas Negeri Makassar. The study aims to address the challenges of disruptions and instability frequently faced by users of Telkom WiFi in the laboratory, causing significant disruptions in internet activities. This instability is exacerbated by simultaneous internet usage, leading to network overload and bandwidth competition among users, ultimately reducing the overall network performance. As a solution, the research proposes the implementation of a network system that integrates Telkom ISP and 3 LTE using the PCC method. The system is equipped with a failover mechanism that automatically redirects the network connection to the active ISP when issues are detected. Additionally, the research categorizes users into admin lecturers and students, imposing bandwidth limitations specifically for students to prevent excessive network traffic. Three in-depth testing scenarios were conducted, demonstrating that the system smoothly redirects internet connections to the active ISP during issues, ensuring uninterrupted and effective internet access for users.